Use of the pasillo for the guitar ensemble of the initial level - Paucar, Diego Elías (Unaciencia, Revista de Estudios e Investigaciones, 2020)
The present work on the use of the corridor for the guitar ensemble of the initial level is intended to provide theoretical information about one of the symbolic musical genres of Ecuador, which is the corridor; as well as one of the most popular musical instruments, the guitarr. The document contains specific information about the corridors, their history and transcendence in the country, as well as the guitar and its structure. Concepts that allow to understand the functionality and importance of the assembly of the initial level in the corridor. As a conclusion it was established that the guitar ensemble in the hall helps to build harmony and sound richness.
Keywords: Array; Array; Array; Array; Array